Us and Them – First-line Management and Change Resistance - Rønningstad, Chris (Nordic Journal of Working Life Studies, 2018)
Change agents are vital in enacting organizational change, yet we know little about the specific challenges first-line managers face in this role.This study draws on written responses from man- agers in Norwegian public welfare organizations to describe the trials of being a change agent. The responses reveal that issues arise from resistance among recipients of the change and from the nature of the manager’s role in the organization. Within these categories, four challenges are delineated: (1) fall-out from ‘change fatigue’, (2) individual resistance to change, (3) managers being caught between two worlds, and (4) a lack of managerial discretion.These challenges could potentially limit the change agent’s efficiency. The study suggests areas for future research and ways for public welfare organizations to improve their change processes